Dissolution and Pharmacokinetic Studies of Paracetamol-4,4′-Bipyridine Cocrystals Obtained Using Four Methods - Xiaoming Zhang; Yejia Huang; Jinliang Li; Yiying Chen; Jialing Lian (Crystals)
Paracetamol-4,4′-bipyridine cocrystals were synthesized using a solution method, reflux method, grinding method, and ultrasonic method. The structures and properties were characterized through the utilization of single-crystal X-ray diffraction (SXRD), powder X-ray diffraction (PXRD), polarized light microscopy (PLM), thermogravimetric analysis (TGA), elemental analysis (EA), and infrared spectroscopy (IR). The results show that the four methods synthesized different cocrystal morphologies, but the same structure and properties coupled with a notably high purity level. All featured strong hydrogen bonds formed between the paracetamol,4,4′-bipyridine and water molecules. An additional notable feature is the presence of π...π stacking interactions between the pyridine rings of adjacent 4,4′-bipyridine molecules. The solubility of paracetamol (active pharmaceutical ingredient, API) and the cocrystal was measured and discussed. In the dissolution experiment, the cocrystal showed a much faster dissolution rate than the API in simulated gastric fluid media (pH = 1.2). Furthermore, the pharmacokinetic (PK) behavior of the cocrystal and the API was investigated to evaluate the effectiveness of this strategy for enhancing the oral absorption of paracetamol. The in vitro and in vivo studies revealed that the paracetamol-4,4′-bipyridine cocrystal possessed an excellent dissolution behavior and an improved pharmacokinetic profile.